2012
DOI: 10.4103/0970-4388.108924
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relation between body mass index, diet, and dental caries among 6-12-year-old children

Abstract: Dental caries scores showed no relationship between BMI-for-age in children. Both snacks and fatty food items were consumed more by obese children, which seeks attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…1) [Willerhausen et al, 2007;Narksawat et al, 2009;Costacurta et al, 2011;Sadeghi et al, 2011;Subramaniam and Singh, 2011;Trikaliotis Higher BMI was associated with lower odds of caries; overweight and obese children were more likely to be primary dental caries free among 7-to 9-year-olds in Guangzhou, China Elangovan et al, 2012;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Shahraki et al, 2013;FriasBulhosa et al, 2015;Denloye et al, 2016;Liang et al, 2016;Pikramenou et al, 2016]. Agreement between the two reviewers was 93% for study selection and 86% for quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1) [Willerhausen et al, 2007;Narksawat et al, 2009;Costacurta et al, 2011;Sadeghi et al, 2011;Subramaniam and Singh, 2011;Trikaliotis Higher BMI was associated with lower odds of caries; overweight and obese children were more likely to be primary dental caries free among 7-to 9-year-olds in Guangzhou, China Elangovan et al, 2012;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Shahraki et al, 2013;FriasBulhosa et al, 2015;Denloye et al, 2016;Liang et al, 2016;Pikramenou et al, 2016]. Agreement between the two reviewers was 93% for study selection and 86% for quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Four main patterns of associations between dental caries and BMI were found among the 14 studies: 5 studies showed no association between caries and BMI [Costacurta et al, 2011;Sadeghi et al, 2011;Elangovan et al, 2012;Frias-Bulhosa et al, 2015;Denloye et al, 2016]; 5 studies found a positive association, namely, that highweight children were more likely to have a higher caries prevalence [Willerhausen et al, 2007;Trikaliotis et al, 2011;Bagherian and Sadeghi, 2013;Shahraki et al, 2013;Pikramenou et al, 2016]; 3 studies showed an inverse association, i.e., that low-weight children were more likely to have a higher caries prevalence [Narksawat et al, 2009;Norberg et al, 2012;Liang et al, 2016]; and there was still 1 study that found a U-shaped pattern, which meant that the deft score was significantly higher in underweight children and there was a higher DMFT score in overweight and obese children [Subramaniam and Singh, 2011].…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations